Analisis Tingkat Pengetahuan Guru Biologi Tentang Model Pembelajaran Discovery Learning di SMA Negeri 1 Bilah Hulu - Ningtyas, Adila Safrani; Siregar, Zunaidy Abdullah; Harahap, Ilham Hakiki (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
The purpose of this study was to see the extent to which the level of knowledge of Biology teachers regarding Discovery Learning influences the improvement of student learning outcomes at the Senior High School level at SMA Negeri 1 Bilah Hulu. This study used a quantitative descriptive approach with analysis using multiple linear regression analysis. The results of the study showed that descriptively Biology teachers at SMA Negeri 1 Bilah Hulu have standards or qualifications where almost 57.7% have higher education. From the results of the hypothesis testing found that there was a good influence between the level of knowledge of Biology teachers regarding the Discovery Learning model. This indicates that the level of knowledge of Biology teachers at SMA Negeri 1 Bilah Hulu Discovery Learning methods in schools is quite good so that in other words Biology teachers continue to follow the development of Discovery Learning. The results of this study indicates that it will affect the success of students in pursuing education, good and regular learning outcomes since or in the process of education are important keys.